The Impact of Macroeconomic and Monetary Policy on the Indonesia Islamic Index - Rachmawaty, Rachmawaty (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
Global economic uncertainties, such as fluctuating commodity prices, geopolitical tensions, and the ongoing effects of the COVID-19 pandemic, continue to influence market dynamics, requiring adaptive monetary policies to support economic recovery and stability. In order to have a better understanding of how monetary policy instruments designed for Islamic finance impact the Sharia stock market and how the uncertainty of macroeconomics can drive the fluctuation of the Sharia stock market, there are two obtained indicators were used, namely Jakarta Islamic Index (JII) represent the liquid stock and Jakarta Islamic Stock Index (ISSI) represent the whole stock in Sharia stock market. The method used ordinary least square using E-VIEWS 10, with independent variables such as money supply, economic growth, inflation, and exchange rate. Data was observed from 2012 up to 2023. The results of this research indicate that JII and ISSI exhibited similar reactions only to changes in inflation. However, their responses diverged regarding changes in the exchange rate, money supply, and economic growth. Notably, a significant impact was observed only from the money supply on ISSI and from the simultaneous effects of the exchange rate, money supply, economic growth, and inflation on ISSI.